Implikasi Sistem Informasi Akuntansi (SIA) Digital dan Peningkatan Efisiensi Operasional terhadap Kinerja Keuangan Berbasis Biaya: Perspektif Budaya Inovasi. - Endang Sriningsih; Nur Azizah Syam; Rusmini (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2025)
This study aims to analyze the impact of digital AIS adoption (X1) and operational efficiency (X2) on cost-based financial performance (Y1), and to test the moderating role of innovative organizational culture (Z). The sample consists of manufacturing companies in Indonesia. PLS-SEM analysis shows that X1 and X2 significantly improve Y1. The moderation results indicate Z strengthens the positive relationship between X1 and Y1, and X2 and Y1. These findings underscore the importance of synergy among technology implementation, efficient operational practices, and an innovative cultural environment to achieve and maintain cost advantage.